Possible role of microRNA miRNA-IL-25 interaction in mice with ulcerative colitis. Issue 1 (1st January 2020) - Yao, Jun; Gao, Ruo-yu; Luo, Ming-han; Wei, Cheng; Wu, Ben-hua; Guo, Li-liangzi; Wang, Li-sheng; Wang, Jian-yao; Li, De-feng
ABSTRACT: Background: The regulatory network of ulcerative colitis (UC)-associated miRNAs is not fully understood. In this study, we aim to investigate the global profile and regulatory network of UC associated miRNAs in the context of dextran sulfate sodium (DSS). Methods: UC was induced in C57BL mice using DSS. Differentially expressed miRNAs were screened by RNA sequencing and subjected to the Kyoto Encyclopedia of Genes and Genomes Pathway enrichment analysis. RT-qPCR was used to verify the differential expression of miRNAs and candidate target mRNA. Luciferase reporter vector bearing a miRNA binding site was constructed to verify the binding site of the miRNA on mRNA. Results:A total of 95 miRNAs (31 were up-regulated and 64 were down regulated) differentially expressed in the colonic tissues of the UC mice. Among the differentially expressed miRNAs, IL-25 pathway genes were enriched. Subsequent RT-qPCR confirmed a decreased expression of IL-25 and a significant up regulation of IL-25 target miRNAs including mmu-miR-135b-5p, mmu-miR-7239-5p and mmu-miR-691 in UC mice. Conclusion: Using the luciferase assay, we verified the biding sites of mmu-miR-135b-5p and mmu-miR-691 to the IL-25 3ʹUTR. In conclusion, mmu-miR-135b-5p:IL-25 and mmu-miR-691:IL-25 interactions are important pathways that may exert a protective role in UC. Graphical abstract: